Arco Cupcakes / Zaid Atul Zan Ariah Binti Abdul Razak, Nur Hazelea Sharleen Binti Bolhassan Alumi and Sulaiman Buyong - Abdul Razak, Zaid Atul Zan Ariah; Bolhassan Alumi, Nur Hazelea Sharleen; Buyong, Sulaiman (2018)
Arco Cupcakes is a partnership company which is wholly owned by a Bumiputera. There are criteria and conditions that have to be fulfilled which required involvement of effort and precision of producing our products. With such conditions, the business can run smoothly and organization goal can be achieved. Along with the cooperation among the executive in this company, we have planned firmly the operation from the administrative till the financial plan in order to equip our company performs with minimum barriers and greater returns. Administration Executive will supervise a unit or section that provides various types of administration support and operating department provides administration of a specific function or program within administrative support department. This person also supervises the staff performance and ensuring the staffs are trained with the purpose to utilize the resources effectively and efficiently. Marketing Executive is responsible to design effective and cost-efficient program in company analysis, marketers focus on understanding the company’s cost structure and cost position relative to competitors, as well as working to identify a firm’s core competencies and other competitively distinct company resources. Marketing Executive liaise with the Financial Executive to analyse the profits of this firm is generating from various services lines and customer accounts. The presence of Operational Manager in this company is responsible to build and maintain strong working relationships with all level of staff in the office. Most important, he will implement standard operating procedures and system in alignment with corporate policies to increase and ensure smooth day-to-day operations. With the continuous cooperation and commitment among us and the other staff, we strongly believe that Arco Cupcakes will be the first place to be visited by the customer who wishes to enjoy quality Cupcakes.